ECONOMIC ANALYSIS OF MARKETING OF GRAPES IN ARGHANDAB DISTRICT, KANDAHAR PROVINCE, AFGHANISTAN - AZIZUL RAHMAN RAGASHTAI, ABDUL RAZIQ REHAN, SURGUL AZIMI, AHMADULLAH BARYALI and (The Journal of Research, PJTSAU, 2021)
The cultivation of domesticated grapes began 6,000-8,000 years ago in Southern Turkey, spreading to Northern Africa, Europe, Asia and North America. More grapes are grown in Afghanistan than any other fruits, comprising nearly half of the total fruits produced, thereby playing an important role in the agricultural economy. Each year grapes are exported (both fresh and dried) to countries such as Pakistan, India, the UAE and Central Asia. Grapes in Afghanistan are consumed fresh, dried and in the form of grape juice. The area of grapes in Afghanistan is about 78405 hectares (2016) of which 90 per cent of this growing area is located in the provinces of Kandahar, Helmand, northern and central zones, (Samadi, 2011). Production of grapes was estimated around 58,000 tons in 2015. Average farm yields are approximately 12.48 tons/ha (United Nation ESCAP, 2018). More than 100 varieties of grapes are grown in Afghanistan, but commercial production focuses on three local varieties; Shindokhani, Kishmishi and Taifi. The grapes are widely famous in Kandahar province as it is main production area for its high quality and productivity. Grapevine orchards are mainly concentrated in Arghandab district with an average yield at about 12.48 tons/ha in Arghandab district from which grapes are supplied to other provinces of the country. Domestic production accounts for the largest part of domestic consumption since very low quantities are imported from abroad. Grapes are the most produced commodity among fruits and vegetables in the country but Afghanistan is barely quoted as a producing country. The area under grapes is gradually increasing in the Arghandab district. So far very few studies have been conducted on the supply chain of grapes in Arghandab district. A detailed study in this regard would help the farmers to have first-hand knowledge of the marketing issues and outcome of the study would be rewarding to the farmers. Hence, this study was undertaken.